Global and Regional Patterns of Longitudinal Strain in Screening for Chemotherapy-Induced Cardiotoxicity - Portugal, G (2017)
INTRODUCTION: Serial echocardiographic assessment of left ventricular ejection fraction (LVEF) is the gold standard in screening for chemotherapy-induced cardiotoxicity (CIC). Measurement of myocardial deformation using speckle tracking enables more detailed assessment of myocardial contractility. The aim of this study was to determine the relationship between global and regional longitudinal strain and CIC. METHODS: This was a prospective study of 158 breast cancer patients undergoing chemotherapy with anthracyclines with or without adjuvant trastuzumab who underwent serial monitoring by transthoracic echocardiography with assessment of myocardial deformation. CIC was defined as a decrease in LVEF to <53%. Global longitudinal strain (GLS) was estimated using EchoPAC BT12 software on a GE Vivid E9 cardiac ultrasound system. Patients were classified according to the 2015 ASE/EACVI criteria as having impaired myocardial deformation when GLS was reduced (less negative), with a cutoff of -18%. RESULTS: During a mean follow-up of 5.4 months (1-48 months), the incidence of CIC was 18.9%. A decrease in GLS was observed during follow-up for the entire cohort (baseline GLS -20.1±3.5% vs. -18.7±3.4% at last follow-up assessment, p=0.001). A total of 97 patients (61.4%) were observed to have impaired myocardial deformation (GLS ≥18%) at some point during follow-up. This decrease was more significant in patients who eventually developed CIC (GLS -17.2±2.5%, p=0.02). On analysis of regional strain, impaired contractility was observed in the septal (6 out of 6) and anterior (2 out of 3) segments. Multivariate logistic regression showed that patients who developed impaired longitudinal strain had a 4.9-fold increased risk of developing CIC (odds ratio 4.88, confidence interval 1.32-18.0, p=0.017). CONCLUSIONS: Worsening of myocardial deformation as assessed by speckle tracking is common in breast cancer patients undergoing chemotherapy, with predominantly septal and anterior wall involvement. Impaired myocardial deformation was independently associated with increased incidence of CIC.